2021
DOI: 10.3390/polym13071153
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Faced Electrostatic Behavior of PNIPAm Microgels

Abstract: PNIPAm microgels synthesized via free radical polymerization (FRP) are often considered as neutral colloids in aqueous media, although it is well known, since the pioneering works of Pelton and coworkers, that the vanishing electrophoretic mobility characterizing swollen microgels largely increases above the lower critical solution temperature (LCST) of PNIPAm, at which microgels partially collapse. The presence of an electric charge has been attributed to the ionic initiators that are employed when FRP is per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 89 publications
(74 reference statements)
3
34
0
Order By: Relevance
“…Such a role, not often recognized in the literature, appears to be important to properly capture the internal modifications of the microgels upon collapse, as also confirmed by electrophoretic mobility measurements across the VPT for a subset of the samples investigated in this work ( SI Appendix , Fig. S2 ) ( 44 , 47 ).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Such a role, not often recognized in the literature, appears to be important to properly capture the internal modifications of the microgels upon collapse, as also confirmed by electrophoretic mobility measurements across the VPT for a subset of the samples investigated in this work ( SI Appendix , Fig. S2 ) ( 44 , 47 ).…”
Section: Resultssupporting
confidence: 61%
“…In a previous work by some of us ( 44 ), the minimum was tentatively associated to the presence of initiator charges, manifesting their effect under collapsed conditions even for simple pNIPAM microgels. This conjecture was supported by electrophoretic mobility measurements also displaying a rapid increase of the signal for temperatures above the VPT, thus providing evidence that, in the high temperature regime, pNIPAM microgels have to be considered as charged micro-objects ( 29 , 47 , 48 ). However, a legitimate doubt concerned whether the minimum in would be solely due to charges or could be attributed to other ingredients, such as the inhomogeneous core–corona topology of pNIPAM microgels synthesized by precipitation polymerization methods.…”
Section: Discussionmentioning
confidence: 68%
“…Likewise, Kleinen and Richtering also provide electrophoresis measurements to investigate the charge inversion of polyelectrolyte-microgel complexes formed by cationic poly(diallyldimethylammonium chloride), PDADMAC, and anionic PNIPAM microgels [ 54 , 55 ]. More recently, Sennato et al have shown that when PNIPAM microgels are collapsed, they strongly interact with oppositely charged polyelectrolytes and a large charge inversion is observed [ 56 ]. In this sense, coarse-grained Monte Carlo simulations have recently been applied to predict the charge inversion previously detected through µ e for nanogel-polyelectrolyte complexes [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…2,[11][12][13] Among polymeric microgels, those made of poly(N-isopropylacrylamide) (PNIPAm) are particularly interesting, since they undergo a Volume Phase Transition (VPT) at ambient temperature: below a characteristic temperature, T c ≈ 32 • C, these colloidal networks exist in a swollen, fully hydrated state, while above T c they collapse due to their increased hydrophobicity. PNIPAm microgels can be synthesized using standard emulsion polymerization in aqueous media 14 and their size, shape and structure have been investigated using various methods including x-ray, light and neutron scattering, [15][16][17][18] and electron or atomic force microscopy. 18 The combination of many different experimental techniques to investigate the VPT of PNIPAm microgels made it possible to grasp a lot of information on this phenomenon, which is one of the most studied in soft condensed matter nowadays.…”
Section: Introductionmentioning
confidence: 99%